2014
DOI: 10.1590/0001-3765201420130512
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance and enterotoxin genes in Staphylococcus sp. isolates from polluted water in Southern Brazil

Abstract: The aim of this study was to evaluate the species distribution, antibiotic-resistance profile and presence of enterotoxin (SE) genes in staphylococci isolated from the Dilúvio stream in South Brazil. Eighty-eight staphylococci were identified, 93.18% were identified as coagulase-negative (CNS) and 6.82% coagulasepositive (CPS). Fourteen Staphylococcus species were detected and the most frequently were Staphylococcus cohnii (30.48%) and S. haemolyticus (21.95%). Resistance to erythromycin was verified in 37.50%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…Other studies from several countries have revealed that S. intermedius and S. pseudintermedius strains are major human infectioncausing agents among coagulase positive staphylococci collected from dogs and cats or in total from animal infections. 26,27 These isolates similar to the studies from Iran, have caused a wide variety of infections. 28,29 There is a need for identification of S. intermedius which has been demonstrated to produce enterotoxins and also other staphylococcal species from livestock specimens in order to prevent or control their transmission to human.…”
Section: The Status Of Zoonotic Staphylococcal Infectionssupporting
confidence: 66%
“…Other studies from several countries have revealed that S. intermedius and S. pseudintermedius strains are major human infectioncausing agents among coagulase positive staphylococci collected from dogs and cats or in total from animal infections. 26,27 These isolates similar to the studies from Iran, have caused a wide variety of infections. 28,29 There is a need for identification of S. intermedius which has been demonstrated to produce enterotoxins and also other staphylococcal species from livestock specimens in order to prevent or control their transmission to human.…”
Section: The Status Of Zoonotic Staphylococcal Infectionssupporting
confidence: 66%
“…In recent years, S. saprophyticus has been described in aquatic environments taken as polluted, such as the marine environment in Lebanon [8] and river flood in Porto Alegre (Brazil) [7]. Here, we observed a high number ( p ≤ 0.01) of S. saprophyticus isolates in Leblon beach, known to receive waters periodically from two fluvial channels carrying untreated domestic sewage.…”
Section: Resultsmentioning
confidence: 52%
“…Despite the numerous reports of this microorganism in food [2–4], the relationship between these findings and the occurrence of UTI in humans has not been demonstrated [5]. In Brazil, S. saprophyticus was described in minas cheese [6], one of the most popular kinds of fresh cheese in the country, and in the water of a polluted river [7]. In addition, reports of S. saprophyticus in the marine environment [8] and food derived from fish [9, 10] draw attention to the spread of this microorganism.…”
Section: Introductionmentioning
confidence: 99%
“…Potentially pathogenic species were among the resistant organisms detected and some of them were multiresistant. Basso et al (2014) 36 report that polluted water from the Dilúvio stream (Porto Alegre, Southern Brazil) may act as a reservoir for the dissemination of antibiotic-resistance and enterotoxin producing Staphylococcus species into the community at large. Together, these studies demonstrate a high degree of antibiotic resistance among environmental bacteria in Brazil and provide evidence that pollution influences the observed diversity among drug-resistant bacteria in these aquatic habitats.…”
Section: Discussionmentioning
confidence: 99%